2016
DOI: 10.1161/strokeaha.116.014091
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Thrombin-Activatable Fibrinolysis Inhibitor and Plasminogen Activator Inhibitor-1 Reduces Ischemic Brain Damage in Mice

Abstract: Background and Purpose-Cerebral ischemia and reperfusion is associated with activation of the coagulation cascade and fibrin deposition in cerebral microvessels. Both thrombin-activatable fibrinolysis inhibitor (TAFI) and plasminogen activator inhibitor-1 (PAI-1) attenuate fibrinolysis and are therefore attractive targets for the treatment of ischemic stroke. Methods-TAFI and PAI-1 were inhibited by monoclonal antibodies in a mouse model of transient middle cerebral artery occlusion. Twenty-four hours after st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 16 publications
4
47
1
1
Order By: Relevance
“…To dissect out the contribution of PAI-1 inhibition and TAFI inhibition during ischaemic stroke, Denorme et al used monoclonal antibodies to identify the effect of inhibiting each of these antifibrinolytic factors. In a mouse model of transient middle cerebral artery occlusion, inhibition of TAFI or PAI-1 significantly decreased fibrin(ogen) deposition in the ischaemic brain, thereby improving reperfusion, but the combined inhibition had an additive beneficial effect [158]. PAI-1 inhibition is also possible with nanobodies, which was demonstrated by Zhou et al who used nanobodies against PAI-1 to inhibit profibrinolytic activity in an in vitro clot lysis assay [159].…”
Section: Current Approaches To Reduce Hypofibrinolysis In Diabetesmentioning
confidence: 99%
“…To dissect out the contribution of PAI-1 inhibition and TAFI inhibition during ischaemic stroke, Denorme et al used monoclonal antibodies to identify the effect of inhibiting each of these antifibrinolytic factors. In a mouse model of transient middle cerebral artery occlusion, inhibition of TAFI or PAI-1 significantly decreased fibrin(ogen) deposition in the ischaemic brain, thereby improving reperfusion, but the combined inhibition had an additive beneficial effect [158]. PAI-1 inhibition is also possible with nanobodies, which was demonstrated by Zhou et al who used nanobodies against PAI-1 to inhibit profibrinolytic activity in an in vitro clot lysis assay [159].…”
Section: Current Approaches To Reduce Hypofibrinolysis In Diabetesmentioning
confidence: 99%
“…While in our study, we have tried to overcome such limitations to arrive at conclusive results. However, a recent study by Denorme et al, 32,33 on murine acute IS model demonstrated that targeting PAI-1 inhibition through a monoclonal antibody helps to attenuate fibrin deposition and improves reperfusion while the bispecific inhibitor against TAFI and PAI-1 results in a prominent profibrinolytic effect in mice without increased bleeding. 31 Genetic variations are quite determining in influencing PAI-1 levels, and the most studied genetic variant, impacting PAI-1 levels, is the 4G/5G promoter polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when intracoronary thrombi aspirated during PPCI were examined, increased von Willebrand factor, P-selectin and fibrin content were related to unfavourable thrombus characteristics rendering the thrombus resistant to lytic therapy (33) and denser plasma fibrin clots were independently associated with high fibrin content (34). Recently, a crucial role of fibrinolysis 18 in determining infarct outcome was shown by combined inhibition of thrombin-activatable fibrinolysis inhibitor and plasminogen activator inhibitor-1, prior to transient cerebral artery occlusion in mice, which reduced cerebral infarct size by 50% (35).…”
Section: Discussionmentioning
confidence: 99%